INVALIDAREA SCRUTINULUI – SANCŢIUNE CA FORMĂ A RĂSPUNDERII CONSTITUŢIONALE - Alexandru ARSENI (Studia Universitatis Moldaviae: Stiinte Sociale, 2019)
The Constitutional responsibility is a form of legal liability that has as its object the activity of the constitutional bodies in the person of the officials (deputies, heads of state). The official nominees accede to position on the basis of the electoral process the only juridical-state mechanism based on the expression of the voters' genuine will. It is this natural and democratic condition that imposes to create the legal and legitimate conditions for the electoral process, including the aggregation of elections. But the creation of these conditions does not guarantee the authenticity of the will of the people as the unique basis of state power. The finality of the process is imposed, without which all intentions may be ineffective. It is also necessary to determine the respective penalties in case of violation of the electoral legislation. These penalties, depending on the stage at which they were detected, must be applied to the subject that committed them. A special situation with special treatment is the falsification of voting results. This illicit deed disturbs and distorts the authenticity of the will of the people in the process of delegating national sovereignty by representativeness to the eligible bodies Deputies, Head of State. It is for these reasons that the penalty is imposed - the invalidation of elections as a form of constitutional responsibility for violation of the electoral legislation. Invalidation entails the declaration of the null vote with the organizing of new elections on the basis of the provisions of the Electoral Code.